Professional learning guide for differentiated instructional strategies : one size doesn't fit all - Gregory, Gayle (Corwin, a SAGE Company, 2013)
Support differentiated instruction schoolwide with this expert guide! The best-selling Differentiated Instructional Strategies: One Size Doesn't Fit All has been revised to include new strategies and a Common Core lesson-planning template-and this workshop-friendly professional learning guide remains the ideal accompaniment. Inside you'll find step-by-step training activities for job-embedded professional development, guidelines for small study groups and larger staff development meetings, and: Guidance for individualized support and mentoring Suggestions for evaluation, coaching, obs.